Interaction between N6-methyladenosine and autophagy in the regulation of bone and tissue degeneration - Wen, Xiaodong; Wang, Junhu; Wang, Qiong; Liu, Peilong; Zhao, Hongmou (Frontiers in Bioengineering and Biotechnology, 2022)
Bone and tissue degeneration are the most common skeletal disorders that seriously affect people’s quality of life. N6-methyladenosine (m6A) is one of the most common RNA modifications in eukaryotic cells, affecting the alternative splicing, translation, stability and degradation of mRNA. Interestingly, increasing number of evidences have indicated that m6A modification could modulate the expression of autophagy-related (ATG) genes and promote autophagy in the cells. Autophagy is an important process regulating intracellular turnover and is evolutionarily conserved in eukaryotes. Abnormal autophagy results in a variety of diseases, including cardiomyopathy, degenerative disorders, and inflammation. Thus, the interaction between m6A modification and autophagy plays a prominent role in the onset and progression of bone and tissue degeneration. In this review, we summarize the current knowledge related to the effect of m6A modification on autophagy, and introduce the role of the crosstalk between m6A modification and autophagy in bone and tissue degeneration. An in-depth knowledge of the above crosstalk may help to improve our understanding of their effects on bone and tissue degeneration and provide novel insights for the future therapeutics.